Aqueous Extract of Nypa fruticansWurmb. Vinegar Alleviates Postprandial Hyperglycemia in Normoglycemic Rats - Yusoff, Nor Adlin; Ahmad, Mariam; Al-Hindi, Bassel; Widyawati, Tri; Mun, Fei Yam; Mahmud, Roziahanim; Abdul Razak, Khairul Niza; Asmawi, Mohd Zaini (MDPI, 2015)
Nypa fruticans Wurmb. vinegar, commonly known as nipa palm vinegar (NPV) has been used as a folklore medicine among the Malay community to treat diabetes. Early work has shown that aqueous extract (AE) of NPV exerts a potent antihyperglycemic effect. Thus, this study is conducted to evaluate the effect of AE on postprandial hyperglycemia in an attempt to understand its mechanism of antidiabetic action. AE were tested via in vitro intestinal glucose absorption, in vivo carbohydrate tolerance tests and spectrophotometric enzyme inhibition assays. One mg/mL of AE showed a comparable outcome to the use of phloridzin (1 mM) in vitro as it delayed glucose absorption through isolated rat jejunum more effectively than acarbose (1 mg/mL). Further in vivo confirmatory tests showed AE (500 mg/kg) to cause a significant suppression in postprandial hyperglycemia 30 min following respective glucose (2 g/kg), sucrose (4 g/kg) and starch (3 g/kg) loadings in normal rats, compared to the control group. Conversely, in spectrophotometric enzymatic assays, AE showed rather a weak inhibitory activity against both -glucosidase and -amylase when compared with acarbose. The findings suggested that NPV exerts its anti-diabetic effect by delaying carbohydrate absorption from the small intestine through selective inhibition of intestinal glucose transporters, therefore suppressing postprandial hyperglycemia.